Linked Data in a Nutshell: A Starter Kit of Selected Annotated Bibliography and Resources for Academic Librarians: Part Two - Weiling Liu (International Journal of Librarianship (IJoL), 2018)
It has been a decade since Tim Berners-Lee coined Linked Data in 2006. More and more Linked Data datasets have been made available for information retrieval on the Web. It is essential for librarians, especially academic librarians, to keep up with the state of Linked Data. There is so much information about Linked Data that one may wonder where to begin when they want to join the Linked Data community. With this in mind, the author compiled this annotated bibliography as a starter kit. Due to the many resources available, this list focuses on literature in English only and of specific projects, case studies, research studies, and tools that may be helpful to academic librarians, in addition to the overview of Linked Data concept and the current state of Linked Data evolution and adoption.